PENINGKATAN PENGETAHUAN KADER KESEHATAN TENTANG APLIKASI GALASEMA DI DESA BANDUNG - Iin Noviana; Pepin Nahariani (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Health services for the elderly are accommodated through the formation of a posyandu for the elderly that can help the community, especially the elderly, to meet their needs to be more optimal. This form of health service is formed by actively and responsibly involving the community. With the formation of health cadres, health services that have been carried out only by health workers can be assisted by the community. Thus, the community is not only an object of development, but also a partner of development itself. To obtain maximum posyandu services, cadres must have a good level of knowledge about posyandu. Knowledge of posyandu cadres is very important as the main guide in carrying out their role in order to provide good health services. Many factors affect the activity of cadres in posyandu, including cadre knowledge about posyandu. Knowledge of cadres will affect the wishes and behavior of cadres in activating posyandu activities so that they can affect the implementation of posyandu work programs. Method: improvement using direct extension method. The target of this counseling is to all elderly posyandu cadres in Bandung Village, Diwek District, Jombang. The implementation method consists of 3 stages, namely: introduction, core, and closing. The results of this activity showed an increase in the knowledge of cadres about the GALASEMA application which can be applied to the elderly to improve the quality of life of the elderly to be more independent.